Country Blues – A Canonically Marginalized Center and the Formation of African-American Aesthetics in Albert Murray’s The Magic Keys - Łobodziec, Agnieszka (Aktualitet - Litteratur, kultur og medier, 2014)
Dr. Agnieszka Łobodziec is Head of the English Section, Uniwersytet Zielonogórski, Poland.